KULTURA A POZNANIE - Duma, Tomasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article deals with the problem of relation between culture and cognition. The author presents the most important manifestations of the crisis of contemporary culture, counting among them the technicization of life, the depersonalization of man and the relativization of value. The main cause of such situation sees in the separateness of culture from nature, and especially from human being’s natural dispositions, among them the principal place has the mind. It concerns first of all the autonomization of culture in respect to cognition, which in recent times significantly has been undergo to relativism, so that the only sphere available to man’s cognition remained his own creativeness. The consequence of it is a closing up of the mind in itself, convicting the culture to exhaustion. As a reason of the culture’s autonomization in relation to cognition author points out the loss of three basic aspects of knowledge, distinguished already by Aristotle – theoretical, practical, and pojetical. A return to this distinction regards as necessary condition to restore the rationality both alone cognition and culture as well. Analysing various aspects of knowledge shows that theoretical cognition is a real basis of all rational human activity, without which any culture cannot arise. In the practical cognition whereas emphasizes an assignment of human action to good, which is its one and ultimate motive, whereof implies that culture-creative are first of all those activities that are motivated by real and not by seeming good. He also notes that pojetical knowledge cannot be reduced to a freely realization of human imagination or creative powers of man, because it is the result of theoretical and practical cognition, expressing in perfecting of the world of nature by imposing upon it the laws of spirit. In the light of what has been said the fundamental purpose of the created by man culture is perfecting of himself in the above-mentioned aspects.